2022
DOI: 10.1038/s41598-022-08423-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-143-3p derived from follicular fluid promotes granulosa cell apoptosis by targeting BMPR1A in polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disorder that occurs in women of reproductive age. Anovulation caused by abnormal follicular development is still the main characteristic of PCOS patients with infertile. Granulosa cell (GC) is an important part of the follicular microenvironment, the dysfunction of which can affect follicular development. Increasing evidence indicates that exosomal miRNAs derived from the follicular fluid (FF) of patients play critical roles during PCOS. However, which follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…When we analyzed the effects on apoptosis, we observed that miR-143 inhibition resulted in a reduction of the apoptosis-related gene, Caspase3, while the miR-143 mimic increased expression of Caspase3 . This finding is supported by those from a previous study demonstrating that miR-143 triggered apoptosis by inhibiting the Smad1/5/8 pathways and regulating the expression of BMP-specific type 1 ( BMPR1A ) [ 11 ]. In addition, an examination of FSHR , a gene target of miR-143 [ 6 ], revealed that miR-143 inhibitors and mimics increased and decreased the mRNA expression of FSHR , respectively.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…When we analyzed the effects on apoptosis, we observed that miR-143 inhibition resulted in a reduction of the apoptosis-related gene, Caspase3, while the miR-143 mimic increased expression of Caspase3 . This finding is supported by those from a previous study demonstrating that miR-143 triggered apoptosis by inhibiting the Smad1/5/8 pathways and regulating the expression of BMP-specific type 1 ( BMPR1A ) [ 11 ]. In addition, an examination of FSHR , a gene target of miR-143 [ 6 ], revealed that miR-143 inhibitors and mimics increased and decreased the mRNA expression of FSHR , respectively.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study in patients with ovarian disease noted that miR-143 was highly expressed in the follicular fluid and further increased apoptosis by inhibiting the Smad1/5/8 pathways [ 11 ]. Research on gastrointestinal disease showed that miR-143 exerted a negative effect, triggering inflammation through the regulation of autophagy by targeting ATG2B [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not thoroughly elucidated which mechanisms are behind the cessation of antral follicle development in PCOS, the apoptosis of GCs triggered by altered follicular niche, for example, androgen excess, was suggested as one of the most potential mechanisms in this regard 65 . Interestingly, an accumulating body of evidence obtained from animal models as well as humans demonstrated that PCOS gives rise to a remarkable increase in GC apoptosis 66–69 . From the molecular perspective, the mRNA expression of numerous p53 target genes was upregulated in GCs of women with PCOS, most of which are implicated in the activation of intrinsic and extrinsic pathways of apoptosis, including BAX, BID, FAS, caspase‐8, and PTEN.…”
Section: Gc Apoptosis In the Pathogenesis Of Pcosmentioning
confidence: 99%
“…8 Several studies reported many differentially expressed miRNAs in exosomes of follicular fluid of PCOS women, which can promote granulosa cell apoptosis and follicular dysplasia. [9][10][11][12] PCOS, as a systemic disease, compromises many organs, not merely the ovaries. Che X et al found miR-27a-5p in serum exosomes was upregulated and affected TGF-β signaling pathways leading to increased risk of endometrial cancer in PCOS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, exosomes and contained miRNAs have been found to be crucial in the pathogenesis of PCOS 8 . Several studies reported many differentially expressed miRNAs in exosomes of follicular fluid of PCOS women, which can promote granulosa cell apoptosis and follicular dysplasia 9–12 . PCOS, as a systemic disease, compromises many organs, not merely the ovaries.…”
Section: Introductionmentioning
confidence: 99%